Application of dexmedetomidine combined with ropivacaine in axillary brachial plexus block in children and its effect on inflammatory factors - Yang, Haikou; Fan, Wei; Yang, Yong; Zhou, Jing; Zhang, Hao; Sun, Jian; Wang, Bo (Cellular and Molecular Biology, 2020)
This study aimed to investigate the effect of dexmedetomidine combined with ropivacaine on inflammatory factors in children with axillary brachial plexus block. Ninety patients who underwent upper limb surgery in our hospital from January 2017 to December 2018 were enrolled and divided into groups A and B. Group A (n=40) was treated with ropivacaine as a local anesthetic, and group B (n= 50) was treated with dexmedetomidine combined with ropivacaine as a local anesthetic during surgery. Face, Legs, Activity, Cry, Consolability (FLACC) Behavioral Pain Assessment Scale was employed to evaluate the pain behavior of the children. Intravenous blood (3 ml) was taken before surgery (T0), 30 min (T1) and 3 hours after surgery (T2) respectively to detect serum TNF-Î± (tumor necrosis factor-Î±), IL-6 (interleukin-6) and IL-1Î² (interleukin-1Î²) levels using ELISA. The adverse reactions in the two groups were observed, and the MAP (mean arterial pressure) and HR (heart rate) were compared before anesthesia, 30 min and 1 hour after block. The FLACC score of both groups showed a marked upward trend (p< 0.001), with that of group B being significantly lower than group A (p< 0.001). Group B presented a remarkably shorter onset time than group A, and the analgesic time was significantly longer (p< 0.001). The incidence of adverse reactions in group B was significantly lower than that in group A (p< 0.05). MAP and HR dropped significantly 30 min and 1 h after block (p< 0.05). MAP and HR were significantly lower in group B than those in group A 30 min and 60 min after block (p< 0.05). As to serum levels of TNF-Î±, IL-6, and IL-1Î², both groups presented notably increased ones after block (p< 0.05). The application of dexmedetomidine combined with ropivacaine in upper limb surgery has a faster onset time and longer duration than ropivacaine alone, which is of certain clinical effect.